An Impact of Liquidity on the Profitability of Commercial Banks in Nepal (A Case Study of Agriculture Development Bank Limited and Nepal Bank Limited) - Neupane, Mukti Prasad; Sapkota, Chet Narayan (Madhyabindu Journal, 2025)
The study examines the relationship between liquidity and profitability in 20 Nepalese commercial banks, focusing on Nepal Bank Ltd. and Agriculture Development Bank Limited. The research used descriptive and causal-comparative approaches, analyzing financial indicators like return on assets (ROA), return on equity (ROE), CR, CRR, CBBISD, and IGSCA. Results showed that liquidity indicators significantly influence profitability, with CR negatively influencing ROA and ROE, CRR weakly influencing ROA and ROE, and IGSCA showing limited influence. The findings underscore the importance of effective liquidity management for enhancing profitability and recommend stable liquidity practices to reduce variability